Longitudinal assessment of network reorganizations and language recovery in postoperative patients with glioma. Issue 2 (6th April 2022) - Yuan, Binke; Zhang, Nan; Gong, Fangyuan; Wang, Xindi; Yan, Jing; Lu, Junfeng; Wu, Jinsong
Abstract: For patients with glioma located in or adjacent to the linguistic eloquent cortex, awake surgery with an emphasis on the preservation of language function is preferred. However, the brain network basis of postoperative linguistic functional outcomes remains largely unknown. In this work, 34 patients with left cerebral gliomas who underwent awake surgery were assessed for language function and resting-state network properties before and after surgery. We found that there were 28 patients whose language function returned to at least 80% of the baseline scores within 3 months after surgery or to 85% within 6 months after surgery. For these patients, the spontaneous recovery of language function synchronized with changes within the language and cognitive control networks, but not with other networks. Specifically, compared with baseline values, language functions and global network properties were the worst within 1 month after surgery and gradually recovered within 6 months after surgery. The recovery of connections was tumour location dependent and was attributed to both ipsihemispheric and interhemispheric connections. In contrast, for six patients whose language function did not recover well, severe network disruptions were observed before surgery and persisted into the chronic phase. This study suggests the synchronization of functional network normalization and spontaneous language recovery in postoperative patients with glioma. Abstract : For patients with glioma involving language networks, Yuan et al . investigated postoperative brain network bases for diverse time courses of spontaneous recovery of language functions. The spontaneous language recovery individually and network-specifically synchronized with the changes of language and cognitive control networks. Graphical Abstract: Graphical Abstract